Avaliação do concreto de cimento portland com resíduo da produção de scheelita em substituição ao agregado miúdo - Paiva, Emanuel Henrique Gomes (2013)
From the 70`s, with the publication of the Manifesto for Environment UN Conference, held in Stockholm, in Sweden (1972), defend and improve the environment became part of our daily lives. Thus, several studies have emerged in several segments in order to reuse the waste. Some examples of waste incorporated in portland cement concrete are: rice husk ash, bagasse ash of cane sugar, powder-stone, microsilica, tire rubber, among others. This research used the residue of the mining industry Scheelite, to evaluate the incorporation of the residue composition of Portland cement concrete, replacing the natural sand. The percentage of residue were incorporated from 0% to 100%, with a variation of 10%, 11 being produced concrete mix in the ratio 1:2:3:0.60, by mass. We evaluated the following characteristics of concrete: slump test, compressive strength, tensile strength by diametral compression, water absorption, porosity and density, based on the ABNT, through tests performed in the Laboratory of Civil Construction, UFRN. The trace with the addition of 60% scheelite residue was obtained which better performance. Therefore, the use of the waste from the production of Scheelite is feasible due to the durability parameters (water absorption and porosity), sustainability, and the good results of the resistance of the concrete